Capacity Building for Public Health: Participant-Guided Training. Issue 6 (November 2020) - Hawley, Suzanne R.; Crimmings, Karen P.; Rivera-Newberry, Ivonne; Orr, Shirley A.; Walkner, Laurie M.
Growth in the demand for public health services, along with limited funding, makes workforce collaboration and capacity building imperative. The faculty and staff of the Midwestern Public Health Training Center, with two Robert Wood Johnson Public Health Nurse Leaders, postulated that training could be more effective, and public health workers more effective in the field, if workers contributed to training format and content. The learning paradigm was tested on diabetes prevention and self-management programs. Public health professionals were surveyed on infrastructure, practices, roles, and gaps in diabetes-related services. Responses influenced the format and content of a one-day diabetes summit training program. Participants submitted evaluations immediately afterward. Eight months postsummit, participants were surveyed to self-assess behavioral changes attributed to the training. Using the Kirkpatrick model for evaluation, participants (n = 112) stated that the training met their expectations and that knowledge gained was consistent with stated training objectives. Qualitative postsummit survey results indicated that improvements in participants' delivery of diabetes prevention services to the public could be attributed to the training they received at the summit. Results suggest that training about specific programs and practices, as well as facilitated sessions of collaboration, can yield individual and organizational change.